2019
DOI: 10.7717/peerj.6609
|View full text |Cite
|
Sign up to set email alerts
|

Phytobiomes are compositionally nested from the ground up

Abstract: Plant-associated microbes are critical players in host health, fitness and productivity. Despite microbes’ importance in plants, seeds are mostly sterile, and most plant microbes are recruited from an environmental pool. Surprisingly little is known about the processes that govern how environmental microbes assemble on plants in nature. In this study we examine how bacteria are distributed across plant parts, and how these distributions interact with spatial gradients. We sequenced amplicons of bacteria from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 48 publications
4
21
0
Order By: Relevance
“…However, studies of cultivated Agave have found that tissue explains more variation in community composition than species and site (27). Tissue type also explains more variation in epiphytic community composition than sample site in the species Scaevola taccada (28). Together, these results suggest that plants are best considered as collections of distinct habitat patches for bacterial colonization.…”
Section: Figmentioning
confidence: 94%
See 1 more Smart Citation
“…However, studies of cultivated Agave have found that tissue explains more variation in community composition than species and site (27). Tissue type also explains more variation in epiphytic community composition than sample site in the species Scaevola taccada (28). Together, these results suggest that plants are best considered as collections of distinct habitat patches for bacterial colonization.…”
Section: Figmentioning
confidence: 94%
“…Recent evidence suggests that within plants, communities in different tissues are composed of a common pool of systemic colonists (24,25). However, individual lineages can display differences in colonization efficiency between roots and stems (26), and several studies have reported variation between the bacterial assemblages found in different tissues (27)(28)(29), supporting the idea that some bacteria are more successful than others in colonizing a given habitat within the plant. Variation in assemblage composition is also observed when plant tissues are sampled at different developmental stages (22,30,31).…”
mentioning
confidence: 99%
“…Terrestrial plants show discrete microbial assemblages and communities dependent upon whether leaves, fruits, or roots are examined (Amend et al, 2019). Similarly, seagrass associated microbes occupy a number of distinct microenvironments across the plant (e.g., the phyllosphere, and the rhizosphere) (Hurtado-McCormick et al, 2019;Wainwright et al, 2019c).…”
Section: Introductionmentioning
confidence: 99%
“…This is clearly corroborated by not only the moderately high values of the network-level indexes of specialization (H2′) and checkerboard score (C-score), but also by the node-level indexes of node and normalized degree, and effective partners and proportional generality. Furthermore, as there was no association between the distance of the sampled trees and their corresponding foliar fungal endophytes community and the environmental conditions are quite the same in sampling area, tree distance most probably serves or as proxy for dispersal limitation or this pattern occurs due to priority effects, and, therefore, are stochastic environmental drivers (Amend et al, 2019) In spite of having worked with culture-dependent foliar endophytic fungal communities along with distinct North-American biomes, Chagnon et al (2016) approximately retrieved these same network-level patterns. Furthermore, Yao et al (2019) working on metabarcoding-analyzed endophytic fungal communities associated with the leaves of six mangrove species, observed that endophytic network structure was characterized by significantly highly specialized and modular but lowly connected and anti-nested properties.…”
Section: Discussionmentioning
confidence: 95%
“…This is clearly corroborated by not only the moderately high values of the network-level indexes of specialization (H2′) and checkerboard score (C-score), but also by the node-level indexes of node and normalized degree, and effective partners and proportional generality. Furthermore, as there was no association between the distance of the sampled trees and their corresponding foliar fungal endophytes community and the environmental conditions are quite the same in sampling area, tree distance most probably serves or as proxy for dispersal limitation or this pattern occurs due to priority effects, and, therefore, are stochastic environmental drivers ( Amend et al, 2019 )…”
Section: Discussionmentioning
confidence: 99%